Integrative review: Evidence and clinical perspectives on the use of botulinum toxin type A in the treatment of congenital muscular torticollis (Research, Society and Development, 2025)
Congenital muscular torticollis (CMT) is a condition characterized by sustained and involuntary contraction of the sternocleidomastoid muscle, resulting in structural changes observed from abnormal tilting, rotation, or flexion of the head. It may be associated with cranial asymmetry, with plagiocephaly being its most common form, and functional limitations. Conservative treatment, based on physiotherapy and stretching, shows good results in most cases, but refractory or late-diagnosed situations still challenge clinical practice. Therefore, this study aimed to analyze the available scientific evidence on the application of biophysical therapy (BPT) in the context of congenital muscular torticollis. This is an integrative literature review, conducted in the electronic databases: PubMed (NCBI, US National Library of Medicine) and BVS (BIREME, PAHO/WHO) using terms properly registered in the Medical Subject Headings (MeSH), delimited by publications between 2005 and 2025. The guiding question applied was: what evidence is available on the use of botulinum toxin type A (TxB-A) in the treatment of chronic musculoskeletal disorders (CMD)? Of the 30 studies identified, only 6 met the eligibility criteria. The findings indicate that TxB-A, especially when associated with physiotherapy, is a safe option with high prognostic effectiveness, mainly in cases refractory to conservative treatment or late initiation of treatment. Despite this, the literature still lacks robust clinical trials and standardized protocols that consolidate its large-scale use.